Characterization of gas-solid two-phase flow by using electrical capacitance tomography - Hamzah, Ahmad Azahari (2020)
Electrical capacitance tomography (ECT) is a non-invasive and non-intrusive internal visualisation modality that allows for better quantification by providing information on the cross-sectional distribution of any kind of multiphase flow. This research is conducted to overcome certain problems in a coal power plant, including the sedimentation of pulverised coal in the piping system before it enters the boiler system and the non-uniformity of its velocity, which leads to a decrease in the production of energy and higher emission of carbon dioxide. To achieve these aims, three objectives are set: (i) determination of the optimum conditions for an AC-ECT system to measure the capacitance of poly(methyl methacrylate) (PMMA) material; (ii) determination of the average solid velocity using a cross-correlation method; and (iii) image reconstruction based on eight ECT sensors using iterative and noniterative algorithms. A simulation of an ECT sensor arrangement was carried out, and a real sensor was then built. Electrical capacitance spectro-tomography was used to obtain the best frequency range to allow PMMA to be analysed using the ECT system. The velocity profile and distribution were calculated using Parseval’s theorem, and signal-to-signal and pixel-to-pixel cross-correlation methods were used, respectively. Iterative and non-iterative image reconstructions were tested for accuracy in a simulation of familiar flow conditions before they were applied to real experimental conditions. The velocity was measured using a dual-plane ECT sensor by applying Parseval’s theorem and an adapted parabolic fit interpolation method, and this gave accurate results with a highest percentage error of 1.94%. An iterative method of image reconstruction based on the Landweber algorithm produced the most accurate results for the visualisation of gas-solid distributions in piping systems, and an acceptable time was required to complete the calculation. This research can help in the optimisation of energy production in coal thermal power plants, and especially in determining the location of coal sedimentation and the velocity of pulverised coal in the piping system.